2008
DOI: 10.1177/0363546508323255
|View full text |Cite
|
Sign up to set email alerts
|

Semitendinosus Tendon Graft versus a Modified Weaver-Dunn Procedure for Acromioclavicular Joint Reconstruction in Chronic Cases

Abstract: Semitendinosus tendon graft for coracoclavicular ligament reconstruction resulted in significantly superior clinical and radiologic outcomes compared to the modified Weaver-Dunn procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
198
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(212 citation statements)
references
References 40 publications
3
198
0
11
Order By: Relevance
“…Contour of the shoulder was maintained and patient was satisfied and pain free joint subluxation and dislocation can be minimized, decreasing the incidence of postoperative pain secondary to residual anterior-posterior instability and compromised clinical outcomes that have been observed with the modified WeaverDunn procedure [25]. Tauber et al reported their experience revising failed Weaver-Dunn procedure with anatomic AC reconstruction with semitendinosus autograft [26]. Significant reduction in pain, improvement in functional scores, and improved radiographic parameters were achieved in their series of revision AC reconstruction cases.…”
Section: Complications From Operative Treatment Of Acromioclavicular mentioning
confidence: 98%
See 1 more Smart Citation
“…Contour of the shoulder was maintained and patient was satisfied and pain free joint subluxation and dislocation can be minimized, decreasing the incidence of postoperative pain secondary to residual anterior-posterior instability and compromised clinical outcomes that have been observed with the modified WeaverDunn procedure [25]. Tauber et al reported their experience revising failed Weaver-Dunn procedure with anatomic AC reconstruction with semitendinosus autograft [26]. Significant reduction in pain, improvement in functional scores, and improved radiographic parameters were achieved in their series of revision AC reconstruction cases.…”
Section: Complications From Operative Treatment Of Acromioclavicular mentioning
confidence: 98%
“…Studies in the literature that directly compare anatomic and nonanatomic techniques show improved results with the anatomic technique [26,47]. Because of the reconstruction technique, repair can be performed in a subacute fashion.…”
Section: Authors' Preferred Treatmentmentioning
confidence: 99%
“…However, studies using graft augmentation have shown to provide superior stability than the modified Weaver-Dunn procedure. 13 In addition, Mazzocca et al 12 described an anatomic graft reconstruction of the conoid and trapezoid ligaments with almost equal biomechanical conditions compared with the native joint.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,11 Laboratory studies showed that anatomic reconstruction with double graft tendons showed native-like biomechanical properties 12 and clinical data showed promising results. 9,13 With the progress of arthroscopic techniques, arthroscopically assisted techniques for graft reconstruction of the AC joint have been described. 10,14 For chronic cases usually open or arthroscopically assisted procedures for graft augmentation have been proposed.…”
mentioning
confidence: 99%
“…Some of these techniques are based on the Weaver-Dunn technique or its modifications. [1][2][3] A number of arthroscopic reconstructions using hamstring graft have been described. 4,5 Our arthroscopic technique is anatomically accurate because it uses a double-bundle coracoclavicular ligament reconstruction with a semitendinosus autograft.…”
mentioning
confidence: 99%